2018
DOI: 10.1088/1361-648x/aab72b
|View full text |Cite
|
Sign up to set email alerts
|

Study of plasmonics in hybrids made from a quantum emitter and double metallic nanoshell dimer

Abstract: We developed a theory for the fluorescence (FL) for quantum emitter and double metallic nanoshell dimer hybrids using the density matrix method. The dimer is made from two identical double metallic nanoshells, which are made of a dielectric core, a gold metallic shell and a dielectric spacer layer. The quantum emitters are deposited on the surface of the spacer layers of the dimers due to the electrostatic absorptions. We consider that dimer hybrids are surrounded by biological cells. This can be achieved by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…With the help of refs. [ 30–32 ] the expressions of SPP and DDI fields are calculated as boldEnormalSPP=normalΛnormalSPPboldEnormalPeiωkteik.boldr,normalΛnormalSPP=RMNP3glrnormals3ςnormalMNP boldEnormalDDI=normalΠnormalDDIboldEnormalPeiωkteik.boldr,normalΠnormalDDI=λsgl3ςnormalMNP…”
Section: Bound States and Density Of States In Random Lasing Nanofibermentioning
confidence: 99%
See 2 more Smart Citations
“…With the help of refs. [ 30–32 ] the expressions of SPP and DDI fields are calculated as boldEnormalSPP=normalΛnormalSPPboldEnormalPeiωkteik.boldr,normalΛnormalSPP=RMNP3glrnormals3ςnormalMNP boldEnormalDDI=normalΠnormalDDIboldEnormalPeiωkteik.boldr,normalΠnormalDDI=λsgl3ςnormalMNP…”
Section: Bound States and Density Of States In Random Lasing Nanofibermentioning
confidence: 99%
“…In the above expression, we have considered normalΛnormalSPP>1because when the probe frequency is in resonance with the SPP frequency, the normalΛnormalSPPhas a very large value. [ 30,31 ] In the derivation of Equation (9), we have also approximated normalΛnormalSPPgnormallζnormalMNP if we put rnormals3RnormalMNP3.…”
Section: Bound States and Density Of States In Random Lasing Nanofibermentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the two-photon fluorescence spectrum split from one peak to three peaks due to dressed states created in the system by strong DDIs 20 . Other similar researches have been done on hybrid materials with quantum dots or other quantum emitters 21,22 .…”
mentioning
confidence: 99%
“…The induced quadrupole moment produces the SPP quadrupole electric field. The field can be calculated using the quasi-static approximation. Let E QP cube be the electric fields produced by the quadrupole moment. By solving the Maxwell equations in the static wave approximation, the electric field produced by the Ag nanocube is calculated as where r c is the distance between the center of Ag nanocube and the center of the QE, and V cube is the volume of the nanocube, and function ζ QP cube is called the polarizability factors and depends on the shape of the Ag nanocube.…”
mentioning
confidence: 99%